If I have an expression x^(-n + 1),
is it correct/safe to do this:
x^(-n + 1) = x^[ -(n - 1) ]
1 / [x^(n - 1) ]
===================================================
If I had (2x + 3)^(-n + 1)
then
(2x + 3)^(-n + 1) = (2x + 3) / [ (2x + 3)^n ]
...........................= (2x + 3) / [ (2x + 3)(2x + 3)^(n - 1) ]
...........................= 1/[ (2x + 3)^(n - 1) ]
But if I just followed
x^(-n + 1) = x^[ -(n - 1) ]
1 / [x^(n - 1) ]
(2x + 3)^(-n + 1) = (2x + 3)^[ -(n - 1) ]
...........................=1/[ (2x + 3)^(n - 1) ]
I'm really not sure if what I'm doing here is correct.